2009
DOI: 10.1111/j.1467-9450.2008.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of self‐conscious emotions: A Swedish psychometric and structure evaluation of the Test of Self‐Conscious Affect (TOSCA)

Abstract: The Test of Self-Conscious Affect (TOSCA) is a well-established scenario-based questionnaire assessing self-conscious emotions, such as shame and guilt, which have been shown to be differentially associated with a variety of functional, motivational, behavioral and health outcomes. The aim of this study was to evaluate the psychometric properties and internal structure of a Swedish version of TOSCA in a sample of 361 healthy adults. The psychometric properties and internal consistency of the Swedish version we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…The known overlap in variance, but differential relationships to health outcomes, regarding the Test of Self-Conscious Affect shame and guilt scales has been discussed in previous studies (e.g., Strömsten, et al, 2009). to address this, guilt-free shame and shame-free guilt, excluding shared variance, were used in the statistical analyses in the present study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The known overlap in variance, but differential relationships to health outcomes, regarding the Test of Self-Conscious Affect shame and guilt scales has been discussed in previous studies (e.g., Strömsten, et al, 2009). to address this, guilt-free shame and shame-free guilt, excluding shared variance, were used in the statistical analyses in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…The Test of Self-Conscious Affect (TOSCA; Tangney, Wagner, & gramzow, 1989) has been used in previous studies to measure shameand guilt-proneness (Averill, et al, 2002;Strömsten, Henningsson, Holm, & Sundbom, 2009). using this scale, feiring and taska (2005) found that abuse-related shame was positively correlated with shame-proneness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kohut (1972) focused on the narcissistic rage that follows the experience of painful shame caused by maternal rejection. This reaction is also endorsed by empirical studies (Strömsten, Henneingsson, Holm, & Sundbom, 2009;Tangney et al, 1992aTangney et al, , 1992bTangney et al, , 1996. Referring to Lewis (1971), Tangney and Dearing (2002b) wrote, a "shamed individual's hostility is initially directed inward, towards the self, the experience is so aversive that there is often an inclination to shift that hostility and blame outward" (p. 91).…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 79%
“…In addition, there may be some overlap between the noninternal attributions, that is, externalization and detachment (Strömsten et al, 2009). We therefore hypothesized a covariance between their error variables (C3 in Figure 1).…”
Section: Methodsmentioning
confidence: 98%